ENGLISH TEACHERS’ PERCEPTIONS OF KAHOOT AS A DIGITAL FORMATIVE ASSESSMENT IN EFL CLASSROOMS: A QUALITATIVE STUDY - Maya Astria; Utami Dewi (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2026)
In English as a Foreign Language (EFL) education in Indonesia, teachers still face various challenges, such as differences in student ability, large class sizes, time constraints, and curriculum requirements that place greater emphasis on final outcomes. This situation has prompted teachers to adopt teaching strategies and resources that can support more effective and sustainable assessment. In this context, Kahoot! has emerged as a practical and easy-to-implement digital platform for the learning process. This is qualitative study examines English teachers’ perspectives on the use of Kahoot as a formative assessment tool in EFL classrooms. Using a phenomenological-constructivist approach, the study involved five EFL teachers who were purposively selected from secondary school. Data were collected through in-depth semi-structured interviews, classroom observations, and document analysis. Data analysis employed a reflexive thematic approach. The analysis yielded four main themes: (1) Kahoot functions as a real-time diagnostic tool, (2) motivational and affective aspects in game-based assessment, (3) pedagogical tensions between entertainment and academic rigor, and (4) contextual and infrastructure-related opportunities and barriers. The results indicate that teachers view Kahoot as a formative instrument capable of providing rapid instructional feedback and enhancing student engagement; however, they also highlight limitations regarding the depth of assessment and its reliability for evaluation purposes. This study offers practical insights into the intersection of gamification, formative assessment, and EFL pedagogy within the Indonesian context.